PENGGUNAAN MEDIA CANVA DALAM PEMBELAJARAN TENTANG PANCASILA SEBAGAI NILAI KEHIDUPAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS IV SD INPRES OEPURA 1 - Sari, Genoveva; Manafe, Yetrusance Y.; Un Lala, Sofia G. (Universitas Nusa Cendana, 2024)
This research was conducted at SD Inpres Oepura 1 with the aim of improving student learning outcomes through the use of Canva media in learning about Pancasila as the value of life in class IV SD Inpres Oepura 1. This research uses the type of class action research (PTK). The subjects in this study were class IVB with a total of 16 students with 10 males and 6 females. Data collection techniques are observation techniques, tests, and documentation. The data analysis technique is descriptive qualitative, with the results of the study indicating that the data from the observation of teacher activities in cycle I with a value of 74.99 and cycle II with a value of 91.66 while the results of observation of student activities in cycle I with a value of 74.99 and cycle II with a value of 89.25. In the cycle I learning cycle that was completed according to KKTP, namely 70 as many as 7 students (44%) while students who did not complete were 9 students (56%). Furthermore, in cycle II of 16 students, 15 students (94%) were completed. Thus it can be concluded that the use of Canva media can improve student learning outcomes in Civics learning material on Pancasila as the value of life in class IVB SD Inpres Oepura 1.